1997
DOI: 10.1046/j.1365-2958.1997.2501619.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of hpuAB, the haemoglobin–haptoglobin‐utilization operon of Neisseria meningitidis

Abstract: SummaryWe previously identified HpuB, an 85 kDa Fe-repressible protein required for utilization of Fe from, and binding to, haemoglobin and the haemoglobin-haptoglobin complex. The gene for hpuB was cloned from Neisseria meningitidis strain DNM2 and the predicted amino acid sequence indicates that HpuB is an outer membrane receptor belonging to the TonB family of high-affinity transport proteins. A second open reading frame, predicted to encode a 34.8 kDa lipoprotein, was discovered 5Ј to hpuB, and was designa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
193
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(197 citation statements)
references
References 60 publications
3
193
0
1
Order By: Relevance
“…However, microbial pathogens have collectively evolved a diverse repertoire of highly effective iron acquisition mechanisms, some of which appear to be specifically "designed" to defeat the ironwithholding system or to target iron-rich niches of the host (3)(4)(5)(6). For example, pathogenic Neisseria species have surface receptors specific for the host extracellular iron-binding proteins transferrin and lactoferrin, turning the two major components of the host iron-withholding system into their iron sources (7,8). Candida albicans possesses mechanisms for attracting and lysing erythrocytes and utilizing the iron in hemoglobin (9,10).…”
mentioning
confidence: 99%
“…However, microbial pathogens have collectively evolved a diverse repertoire of highly effective iron acquisition mechanisms, some of which appear to be specifically "designed" to defeat the ironwithholding system or to target iron-rich niches of the host (3)(4)(5)(6). For example, pathogenic Neisseria species have surface receptors specific for the host extracellular iron-binding proteins transferrin and lactoferrin, turning the two major components of the host iron-withholding system into their iron sources (7,8). Candida albicans possesses mechanisms for attracting and lysing erythrocytes and utilizing the iron in hemoglobin (9,10).…”
mentioning
confidence: 99%
“…No known homologues of HpuA exist in public databases, and its role in HpuAB function remains to be determined. We have reported data suggesting that HpuA and HpuB physically interact to form a functional receptor complex (51,69). Characterization of isogenic single mutants of HpuA and HpuB suggested that both receptor components are absolutely required for the utilization of Hb or HbHp (48,69).…”
mentioning
confidence: 99%
“…This model was based on the highly conserved three-dimensional X-ray crystallographic structures of three E. coli TonB-dependent siderophore receptors: FepA, FhuA, and FecA (6,(23)(24)(25)52). The 35-kDa HpuA accessory lipoprotein is peripherally associated with the OM via an N-terminally linked fatty acid tether (49,69). No known homologues of HpuA exist in public databases, and its role in HpuAB function remains to be determined.…”
mentioning
confidence: 99%
See 2 more Smart Citations